InP nanopore arrays for photoelectrochemical hydrogen generation. (18th January 2016) - Li, Qiang; Zheng, Maojun; Zhang, Bin; Zhu, Changqing; Wang, Faze; Song, Jingnan; Zhong, Miao; Ma, Li; Shen, Wenzhong
Abstract: We report a facile and large-scale fabrication of highly ordered one-dimensional (1D) indium phosphide (InP) nanopore arrays (NPs) and their application as photoelectrodes for photoelectrochemical (PEC) hydrogen production. These InP NPs exhibit superior PEC performance due to their excellent light-trapping characteristics, high-quality 1D conducting channels and large surface areas. The photocurrent density of optimized InP NPs is 8.9 times higher than that of planar counterpart at an applied potential of +0.3 V versus RHE under AM 1.5G illumination (100 mW cm −2 ). In addition, the onset potential of InP NPs exhibits 105 mV of cathodic shift relative to planar control. The superior performance of the nanoporous samples is further explained by Mott–Schottky and electrochemical impedance spectroscopy ananlysis.